Ischemic Tolerance Evaluated by Computed Tomography Perfusion During Balloon Test Occlusion. (16th November 2020) - Kuribara, Tomoyoshi; Mikami, Takeshi; Iihoshi, Satoshi; Miyata, Kei; Kim, Sangnyon; Kawata, Yuka; Komatsu, Katsuya; Kimura, Yusuke; Enatsu, Rei; Akiyama, Yukinori; Hirano, Toru; Mikuni, Nobuhiro
Abstract: INTRODUCTION: Balloon test occlusion (BTO) is performed to evaluate ischemic tolerance for large and giant cerebral aneurysms and head and neck tumors that may require parent artery occlusion. However, ischemic tolerance for the temporary test occlusion does not always guarantee a tolerance for permanent occlusion. METHODS: Forty-one patients who underwent BTO for the internal carotid artery were included. The correlations between the parameters of CT perfusion and collateral angiographic appearance or stump pressure during BTO were evaluated. The cerebral blood flow (CBF), cerebral blood volume (CBV), mean transit time (MTT), and time to peak (TTP) were obtained through CT perfusion, and the asymmetry ratios were determined. Collateral angiographic appearances were categorized into five grades (0-4). RESULTS: The collateral angiographic appearance showed moderate correlations with CBF, MTT, and TTP that was significant. Of these, the absolute value of the correlation coefficient was the highest for MTT. MTT also showed a moderate correlation with stump pressure. CBF and MTT were significantly different between the poor collateral group (grades 2 and 3) and the good collateral group (grade 4). Based on the MTT, the good collateral group was identified with high sensitivity (75.0%) and specificity (81.2%). CONCLUSION: In BTO, the MTT obtained through CT perfusion showed a correlation with collateral angiographic appearance and stump pressure. Thus, the MTT might be useful to quantify ischemic tolerance for detecting delayed ischemic stroke.